Work Motivation as a Mediator of the Influence of Leadership Style and Work Environment on Employee Work Discipline at PT. Pertamina Patra Niaga Integrated Terminal Palembang - Sari sakarina; Farah Raudha Fitrinia; Rosalina Pebrica Mayasari (Pascasarjana, Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2026)
Work discipline is a crucial factor in ensuring operational effectiveness, especially in companies engaged in the energy distribution sector. This study aims to analyse the influence of leadership style and work environment on employee work discipline with work motivation as a mediating variable at PT. Pertamina Patra Niaga Integrated Terminal Palembang. The study uses a quantitative approach with a survey method targeting permanent employees. Data was collected through questionnaires and analysed using path analysis. The results show that leadership style and work environment have a positive and significant effect on work motivation. Work motivation also has a positive and significant effect on work discipline. Furthermore, work motivation was found to mediate the influence of leadership style and work environment on employee work discipline. These findings emphasise the importance of effective leadership and a conducive work environment in enhancing employee motivation and work discipline in the energy distribution sector.